INFORMATION SYSTEM’S IMPLEMENTATION ON GOVERNANCE QUALITY AND ITS IMPACT ON UNIVERSITY ORGANIZATION PERFORMANCE : Implementación de sistemas de información en la calidad de gobernanza y su impacto en el rendimiento de la organización universitaria - HAYATI, U.; MULYANI, S.; SUKARSA, D.E.; WINARNINGSIH, S. (Utopía y Praxis Latinoamericana, 2021)
This study aims to determine the effect of information systems’ implementation success on governance quality and its impact on university organization performance. This study uses descriptive statistical analysis and verification analysis using the Structural Equation Model (SEM). Data collection was conducted through an online questionnaire distributed to 163 universities in West Java with accreditation B and C. The findings indicate that the success of information systems’ implementation also has a positive effect on the performance of university organizations in West Java through the quality of governance.